Targeting FoxP3 gene to check out the impairment of tolerance in breast cancer patients - N. Hussain; N. Mahmood; A.N. Sabri (Journal of King Saud University: Science, 2022)
Objective: FoxP3 gene is a potential gene in the development of Breast Cancer (BC). Mutated expression of this gene shows some correspondence with tumorigenic activity for this reason it is important to understand. The principal goal of this study was the mutational analysis of the FoxP3 gene in BC patients. This research also provides the basic functions and genetic details on the FoxP3 gene in the Lahore population, especially how the FoxP3 gene acts as a risk factor in BC development. The study design was Cross-sectional. Methods: Genomic DNA was extracted from peripheral blood samples of BC patients. Amplified products were electrophoretically separated and target PCR products were sequenced with a Sanger sequencing analyzer. The main purpose is to determine the order of nucleotides in the FoxP3 gene. Further mutations were analyzed by the chromatograms using Chromas, NCBI nucleotide BLAST X, and the Mutation Surveyor. After that, different protein-coding sequences were studied. Results: The substitution occurs at location 324 where T is replaced by A and in another sample G is replaced by A at position 328 while in the third sample InDel mutation was observed at position 28. Conclusion: In the current study, intronic variants typically in the FoxP3 gene exon 2 region were confirmed by computational analysis using a gene database. We investigated nucleotide mutations in FoxP3 in patients with malignant breast tumors, along with their association with various characteristics such as marriage status, age of menopause, miscarriage and lactation history, and family history. A better understanding of the FoxP3 gene in the etiology and progression of breast cancer can reveal many explorable problems, including the clinical implications of the FoxP3 gene. However, these intronic variations are of massive importance and demonstrated that this enhancer can establish a physical interaction with a promoter site binding nuclear factor-κB components necessary for T cell regulation.